(3GdEbfGY aj Md CdaGX CHj TLGYs - (3GdTQHjfj GdeUQj GdTGaYj, TeS GdOjf (B- (3GdNWjH, eMeO Hf CMeO, J (B977 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH HjGf CMcGe GdaQGjV hGdhUGjG ; GdaQGjVeY aQjVI HeYfi eaQhVI Cj ebOQI deG ajgG ef GdSgGe GdebOQIs
(3BNQgG (B:s
(3adh cGf dg faS fGWbI hdSGf efWdb dbGd HebGd UQjM hcdGe aUjM ddg OQ eDda gPG GdJCdja GdQGjb GdQjSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 6s
(3eYLe GdeDdajf (B3 / 69s
(3EjVGM Gdecfhf (B2 / 448s
(3TPQGJ GdPgH (B8 / 384s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs